Problem-based learning model: It’s effect on mathematical literacy ability based on students' visual verbal ability - Syafitri, Aulia; Huda, Nizlel; Haryanto, Haryanto (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This study was conducted at SMP Negeri 9 Jambi City to determine the effect of the Problem-based Learning (PBL) model on mathematical literacy skills in the Pythagorean Theorem material. The quasi-experimental design was used with a non-equivalent pretest and posttest control group design. The researchers collected the mathematical literacy ability data using a description test instrument. Furthermore, the visual-verbal ability data was collected using a visual-verbal ability questionnaire. This research was conducted on the seventh-grade students, with 69 students divided into two classes (experimental and control classes). A random sampling technique determined the sample. Based on the two-way ANOVA test, applying the Problem-based Learning (PBL) model on students' mathematical literacy skills was an effect. There was an effect of visual-verbal ability on literacy skills.